(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the authors analyzed the coverage of the technology of developing analytical thinking among future teachers in the research of foreign scientists, revealed the essence of the concept of analytical thinking and its specificity on a scientific and theoretical basis. At the same time, trends in the development of analytical thinking, strengthening intellectual potential, increasing the spiritual and ideological immunity of future teachers, and consolidating information skills are revealed. The article substantiates the importance of the formation of analytical thinking among future teachers, analyzes the current state of the development of analytical thinking in modern higher educational institutions, as well as the possibilities and ways of solving problems to eliminate shortcomings. The technologies and models developed by research scientists from foreign countries for the development of analytical thinking are considered in detail, and their significance and relevance are assessed. The formation and comparison of analytical thinking occurs only in practical activities. Listening to recommendations and instructions on the formation of analytical thinking, listening to lectures, the student does not acquire such an ability. Real academic qualifications are formed in practice. The use of interactive methods in the formation and development of analytical thinking among students is becoming important. Preparing students for analytical activities plays an important role in achieving harmony between external and internal factors. The "PRBL“ model of Indonesian researchers teaches students how to create a need for analytical activity and effectively implement this process. Achieving harmony between the content of the model and the stages of its implementation ensures the effectiveness of preparing students for analytical activities.